Enhanced TH17 responses in patients with IL10 receptor deficiency and infantile-onset IBD - Shouval, D; Konnikova, L; Griffith, A; Wall, S; Biswas, A; Werner, L; Nunberg, M; Kammermeier, J; Goettel, J; Anand, R; Chen, H; Weiss, B; et al. (Oxford University Press, 2017)
Background IL10 receptor (IL10R) deficiency causes severe infantile-onset IBD. Intact IL10R-dependent signals have been shown to be important for innate and adaptive immune cell function in mice. We have previously reported a key role of IL10 is the generation and function of human anti-inflammatory macrophages. Independent of innate immune cell defects, the aim of the current study was to determine the role of IL10R signaling in regulating human CD4+ T cell function. Methods Peripheral blood mononuclear cells and intestinal biopsies cells were collected from IL10/IL10R-deficient patients and controls. Frequencies of CD4+ T cell subsets, naïve T cell proliferation, regulatory T cell (Treg)-mediated suppression and Treg and TH17 generation were determined by flow cytometry. Transcriptional profiling was performed by NanoString and quantitative real-time PCR. RNA in situ hybridization was used to determine the quantities of various transcripts in intestinal mucosa. Results Analysis of 16 IL10- and IL10R-deficient patients demonstrated similar frequencies of peripheral blood and intestinal Tregs, compared to control subjects. In addition, in vitro Treg suppression of CD4+ T cell proliferation and generation of Treg were not dependent on IL10R signaling. However, IL10R-deficient T naïve cells exhibited significantly higher proliferative capacity, a strong TH17 signature and an increase in polarization towards TH17 cells, compared to controls. Moreover, the frequency of TH17 cells was increased in the colon and ileum of IL10R-deficient patients. Finally, we show that stimulation of IL10R-deficient Tregs in the presence of IL1 leads to enhanced production of IL17A. Conclusions IL10R signaling regulates TH17 polarization and T cell proliferation in humans, but is not required for the generation and in vitro suppression of Tregs. Therapies targeting the TH17 axis might be beneficial for IL10- and IL10R-deficient patients as a bridge to allogeneic hematopoietic stem cell transplantation.